What attributes do consumers seek when buying vegetables: the case of East Timorese consumers - Correia, Vincente; Rola-Rubzen, Maria Fay (World Business Institute, 2012)
In recent years, there has been a change in consumer attitudes towards food in general, and vegetables, in particular. Recent health and food scares as well as the increasing concern over pesticide use and food safety have made consumers more selective and demanding in terms of the quality of food. This paper outlines the results of a study on the attributes consumers seek when buying high value vegetables (carrots, snow peas and cabbages) in Timor Leste. The study was conducted in Dili and Baucau, the two major districts in the country. The study found that when buying these high value vegetables, the attributes Timorese consumers seek are that the product is free from physical damage, is fresh, is free from pest and diseases, free from chemical residues and is competitively priced. Furthermore, consumers have a high expectation for producers to meet these attributes.